A Cross Sectional Study on Thrombocytopenia with Mean Platelet Volume and Platelet Distribution Width in Patient with Febrile Illness - Vidhya.G; J.Margaret Theresa; J.S. Sukanya; Santha Sandasivan; Gerard Rakesh. J (National Board of Examinations Journal of Medical Sciences)
Introduction: Thrombocytopenia is characterized by reduced platelet count, affecting men and women equally. It is usually associated with conditions such as febrile illnesses like dengue fever, malaria, and other infectious etiology. The causes of thrombocytopenia can be evaluated by studying the platelet parameters. Aim: Investigating the clinical and pathological characteristics of Acute Febrile Illness and Assessing Thrombocytopenia Using Mean Platelet Volume and Platelet Distribution Width. Materials and Methods: Study was conducted on 85 individuals, both male and female, aged between 18 and 65 years, who presented with thrombocytopenia and acute febrile infections. The cases of thrombocytopenia were classified as mild, moderate, or severe, and peripheral smears were performed on all 85 cases to rule out pseudothrombocytopenia. Several subgroups were also derived after evaluating the etiology of thrombocytopenia. Results: In all 85 individuals who presented with thrombocytopenia, MPV and PDW values were calculated. There was an increase in MPV and PDW values on day 1 compared to the values on day 2 and day 3. Thrombocytopenia severity was categorized as mild, moderate, or severe based on the MPV and PDW values. Conclusion: Platelet volume parameters such as mean platelet volume (MPV) and platelet distribution width (PDW) offer valuable insights into the mechanisms of thrombocytopenia. PDW, in particular, plays a critical role among these parameters. When assessed alongside other parameters, PDW can provide important information about the mechanisms behind platelet destruction.